Penerapan Sistem Kanban untuk Meningkatkan Efisiensi Pengelolaan Material di Gudang: Studi Kasus : PT. Soemo Adjie Persada - Yunisa Nurmala Sari; Anita Oktaviana Trisna Devi; Bekti Nugrahadi (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
PT. Soemo Adjie Persada is a company engaged in housing development and is dealing with serious problems in warehouse material management. The manual and unstructured material recording system causes various obstacles, such as data discrepancies, input errors, and stockouts that hamper the smooth running of the project. This study aims to analyze and implement the Kanban system as a more efficient and accurate material management solution. The study was conducted using a qualitative descriptive approach through interviews, observations, and documentation methods. The findings show that the Kanban system, which is based on the principle of workflow visualization and a pull system mechanism, can improve the efficiency of recording and distributing materials between project units. The implementation of Kanban helps reduce data input errors, prevent material loss, and accelerate the decision-making process in the warehouse. Although challenges such as damaged Kanban cards and difficulty adapting among users were encountered in the initial implementation stage, these obstacles can be overcome through proper training and regular evaluation of the system. Thus, the implementation of the Kanban system has proven to be an effective strategy in improving the efficiency of material management in construction projects. This system not only streamlines warehouse operations but also improves control over material availability, thereby supporting the smooth running of the overall construction process. PT. Soemo Adjie Persada is a company engaged in housing development and is dealing with serious problems in warehouse material management. The manual and unstructured material recording system causes various obstacles, such as data discrepancies, input errors, and stockouts that hinder project progress. This study aims to analyze and implement the Kanban system as a more efficient and accurate material management solution. The study was conducted using a qualitative descriptive approach through interviews, observation, and documentation.